Pembelajaran Case Based Learning Untuk Meningkatkan Hasil Belajar Fisika Pada Peserta Didik Kelas X MIPA 1 SMAN 3 Maros - Nurfadillah Nurfadillah; Nurul Amalia Ramadani; Nurul Magfirah; Nurul Wahyuni Dewi (Journal Innovation In Education, 2024)
This research was conducted to determine the increase in student learning outcomes at SMA Negeri 3 Maros Class X MIPA 1 by applying the Case Based Learning (CBL) learning model. This study uses a quantitative method with the type of classroom action research (CAR). The subjects of this study were 33 students. Based on the research results in cycle I, the average pre-test score was 56.21 and the post-test score was 67.72. This score shows an increase of 11.51 points with a standard n-gain of 0.26 and is classified as low, then the research data for cycle II The average value of the pre-test is 70.75 and the post-test is 89.54, an increase of 18.79 point. The standard n-gain in cycle II is 0.64 with moderate qualifications. From these data it can be seen that the standard gain for studying physics has increased in each cycle and is classified as a moderate qualification in Cycle II.